On the evaluation of negative altitude requirement for flutter speed boundary of transport aircraft and UAV - Sulaeman, Erwin (Trans Tech Publications Ltd., Switzerland, 2012)
To maintain flight safety, all transport aircraft designs should satisfy airworthiness standard regulation. One fundamental issue of the aircraft design that relates directly to flight safety as well as commercial aspect of the aircraft is on the evaluation of the maximum speed within the designated flight envelope. In the present work, a study is performed to evaluate the negative altitude requirement related to aeroelastic instability analysis as one requirement that should be fulfilled to design the maximum speed. An analytical derivation to obtain the negative altitude is performed based on the airworthiness requirement that a transport airplane must be designed to be free from aeroelastic instability within the flight envelope encompassed by the dive speed or dive Mach number versus altitude envelope enlarged at all points by an increase of 15% in equivalent airspeed at both constant Mach number and constant altitude. To take into account variation in atmospheric condition as function of altitude, the international standard regulation is used as referenced. The analysis result shows that a single negative altitude can be obtained using these criteria regardless of the dive speed or dive Mach number. A further discussion on the application of the negative altitude concept to UAV (Unmanned Aerial Vehicle), in relation to UAV Standard Airworthiness Requirement STANAG 4671, is presented.